Amostragem de grãos em silos para análise de micotoxinas e impacto micotoxicológico e nutricional de híbridos de milho no custo da ração de frangos - Mallmann, Adriano Olnei (2018)
Cereals stored in silos can be contaminated by mycotoxins, which are distributed heterogeneously in the grain mass. Thus, they require representative sampling in order to minimize the analytical error. Higher requirements for maize and wheat quality have arisen with new demands and research results. Around 70% of poultry and pork production costs are composed of feed wich maize have the largest percent of inclusion in the diet. For safe diet formulation, adequately nutritional requirements for animals are necessary, and for this it is important to consider the mycotoxins risks and the chemical and energetic composition of the ingredients. The objective of the first study was to compare mycotoxin detection analysis in stored maize and wheat using two sampling processes and in the second study was to evaluate the mycotoxicological and nutritional variables of maize hybrids with different characteristics that influence the broiler chickens feed costs. In the first study, a pneumatic probe was introduced in the centre and at the four central points of each quadrant, from the top to the bottom of the silo (12 m). For sampling process A, this was divided into three samples (upper third, middle third and lower third of the silo height). No sample subdivision took place for sampling process B. Aflatoxins (AFLA), fumonisins (FUM), zearalenone (ZEA) were detected in the maize samples, with a difference in the mean concentration of the silos. In wheat, deoxynivalenol (DON) and ZEA were detected, with no difference in the mean concentration in the silos. The two sampling processes provide results of analyzes with the same variability in maize and although process A has lower variability for DON in wheat, the two processes provide samples with the same representativity considering the silo as a whole, supporting the decision making in the maize purchase, sale and destination of the grains. In the second study, evaluating 26 genetically modified maize hybrids of 2016 and 2017 winter crops, with different germplasm, endosperm grain texture and cycle length, the prevalence of FUM, AFLA, ZEA and DON was 90, 17, 33 and 0%, with means of 3067, 1, 38 and 0 μg/kg in the two years, respectively. The mean apparent metabolizable energy corrected for nitrogen balance (AMEn) and crude protein (CP) was 3264 kcal/kg and 8.02%, respectively, and differed in the two years. The estimated feed for broilers chickens cost was influenced by FUM, PB, AMEn in the two years. Hybrids with Viptera technology show lower concentration per FUM and lower feed cost. Early cycle hybrids have lower concentrations of FUM, higher percentages of CP and digestible amino acids, and lower feed costs.